2012
DOI: 10.4038/josuk.v6i0.4221
|View full text |Cite
|
Sign up to set email alerts
|

An integrated approach to the management of rice root knot nematode, Meloidogyne graminicola in Sri Lanka

Abstract: This study was carried out to design tools for integrated management of root knot nematode, Meloidogyne graminicola, in rice in Sri Lanka. Rice varieties namely, At5,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Besides alternative hosts and irrigation, the soil type influenced the tolerance of plants to Mg and showed differences in the multiplication of the nematode [ 91 ]. Studies have also revealed that infestation levels depend on the rice cultivar [ 117 , 118 ], and the aggressiveness differs between populations, suggesting intraspecific variability [ 35 , 119 ]. It was also found that Mg consists of more than one race.…”
Section: Damage/crop Losses In Ricementioning
confidence: 99%
“…Besides alternative hosts and irrigation, the soil type influenced the tolerance of plants to Mg and showed differences in the multiplication of the nematode [ 91 ]. Studies have also revealed that infestation levels depend on the rice cultivar [ 117 , 118 ], and the aggressiveness differs between populations, suggesting intraspecific variability [ 35 , 119 ]. It was also found that Mg consists of more than one race.…”
Section: Damage/crop Losses In Ricementioning
confidence: 99%
“…Moreover, some mechanisms are involved for the explanation of toxic effect of the tested organic amendments such as the release of ammonia, fatty acids, induce the plant tolerance and create unsuitable atmosphere in the soil for nematode behavior (Thoden et al, 2011;Chindo et al, 2012). In addition, soil amended with organic materials will promote plant growth due to the availability of nutrients during the decomposition of these amendments which significantly inhibited the nematode population (Amarasinghe, 2011). Phytochemical constituents released during the decomposition of B. spectabilis were cyanogenic glycosides, quinones, saponins, triterpenoids, flavonoids, alkaloids, sterols, tannins, furanoids and phenols (Francisco and Pinotti 2000;Umamaheswari et al, 2008).…”
Section: Statistics Analysismentioning
confidence: 99%
“…It has been found that there is a decline of rice yield when more than 75% of the roots of an infested plant is affected by nematodes (Nugaliyedde et al, 2001). Experiments have proven that infestation level varies based on the rice variety (Amarasinghe, 2011;Amarasinghe et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Use of resistant rice varieties can also be implemented to keep the nematode population under control. Bg 352, Bg 300 and Bg 357 are some of the existing rice varieties identified as resistance to the nematode infestation in Sri Lanka (Amarasinghe et al, 2011). Several indices have been developed to identify the level of resistance of different crop varieties.…”
Section: Introductionmentioning
confidence: 99%